Anteseden Consumer Buying Behavior - Bima Farras Suddywo; Ayu Ekasari (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This research aims to analyze the consumer buying behavior consequential variables consisting of, Ecolabeling, Green Branding, Green Advertising, Environmental Knowledge, and Green Consumption. The sampling method used is non-probability sampling with purposive sampling technique. A total of 200 respondents had purchased or knew about environmentally friendly products and had ecolabeling labels. Data was collected through a cross-sectional questionnaire. Then the data was analyzed using SEM Structure Equation Modeling. The results of hypothesis testing show that there is a positive influence of Ecolabeling, Green Advertising, Green Branding, Environmental Knowledge, Green Consumption on Consumer Buying Behavior. The results of this research can provide input for entrepreneurs or companies that make environmentally friendly electronic products to further increase their green marketing and also product sales.